N-Acetylcysteine Attenuates the Increasing Severity of Distant Organ Liver Dysfunction after Acute Kidney Injury in Rats Exposed to Bisphenol A - Wachirasek Peerapanyasut; Anongporn Kobroob; Siripong Palee; Nipon Chattipakorn; Orawan Wongmekiat (MDPI AG, 2019)
Distant organ liver damage after acute kidney injury (AKI) remains a serious clinical setting with high mortality. This undesirable outcome may be due to some hidden factors that can intensify the consequences of AKI. Exposure to bisphenol A (BPA), a universal chemical used in plastics industry, is currently unavoidable and can be harmful to the liver. This study explored whether BPA exposure could be a causative factor that increase severity of remote liver injury after AKI and examined the preventive benefit by N-acetylcysteine (NAC) in this complex condition. Male Wistar rats were given vehicle, BPA, or BPA + NAC for 5 weeks then underwent 45 min renal ischemia followed by 24 h reperfusion (RIR), a group of vehicle-sham-control was also included. RIR not only induced AKI but produced liver injury, triggered systemic oxidative stress as well as inflammation, which increasing severity upon exposure to BPA. Given NAC to BPA-exposed rats diminished the added-on effects of BPA on liver functional impairment, oxidative stress, inflammation, and apoptosis caused by AKI. NAC also mitigated the abnormalities in mitochondrial functions, dynamics, mitophagy, and ultrastructure of the liver by improving the mitochondrial homeostasis regulatory signaling AMPK-PGC-1α-SIRT3. The study demonstrates that NAC is an effective adjunct for preserving mitochondrial homeostasis and reducing remote effects of AKI in environments where BPA exposure is vulnerable.